Percepções das identidades sociais de raça/etnia e gênero na escola: vozes de professoras e alunos/as. - Ferreira, Susana Aparecida (2011)
The main objective of this work is to investigate the way students of fundamental levels are represented in theirs school´s books and materials - more specifically, English students and two 8th grade classes, and if they identify themselves being represented in race/ethnicity and gender in these materials. On other hand, I also noticed how the fundamental school teacher perceives the construction of the social identities and if him also perceives those same identities been worked out in the instructional materials and books being utilized, and the way that the English Teacher has to deal with social identity in class. In Brazil we have the cognitive perspective of the functionality of Foreign Language teaching as a social aspect, utilizing Critical Literacy, Paulo Freire (1980), Lankshear e Maclaren (1993), Norton (1995), Comber e Kalmer (1997), Pennycook (1998), Busnardo e Braga (2000), Rajagopalan (2003), Ferreira (2006), Jordão (2007), Coradim (2008), identidades sociais, Moita Lopes (2002), Jung (2002), Hall (2002-2006), Carvalho (2007), Carvalho (2007), among others. For the methodological development I made use of questionnaires and interviews. As the result of this research, I was able to perceive that the practical aspect is far from being achieved. However, teachers state that they realize the importance of critical teaching about race/ethnicity and gender in their classes, but yet they aren´t able to insert this matters in their daily learning routine, subject that extend to their students and they aren´t able too, to perceive themselves in their learning materials nor develop an array of learning of these matters, especially about gender. I conclude betting that the efficiency of the critical teaching has a way to change this matters, as the lack of critical sense in the classroom, the empowerment of the students, allowing their voice to be heard, both at school and in the other social contexts that they are inserted.